Comparative gut transcriptome analysis reveals differences between virulent and avirulent Russian wheat aphids, Diuraphis noxia - Anathakrishnan, Radhika; Sinha, Deepak K.; Murugan, Marimuthu; Zhu, Kun Yan; Chen, Ming- Shun; Zhu, Yu Cheng; Smith, C. Michael (My University, 2014)
The Russian wheat aphid, Diuraphis noxia, is a destructive pest of cereal crops that exhibits virulence to D. noxia resistance genes in wheat. Therefore, it is important to identify D. noxia virulence factors. The insect gut, the primary site of defense to ingested toxins, is also a likely site of differential gene expression in virulent insects. Comparative analyses of gut transcriptomes from virulent and avirulent D. noxia can improve an understanding of aphid gut physiology and may reveal factors critical to compatible D. noxia-wheat interactions. A total of 4, 600 clones were sequenced from gut cDNA libraries prepared from avirulent (biotype 1) and virulent (biotype 2) D. noxia feeding on biotype 1-resistant wheat. A majority of the sequences (66% in biotype 1, 64% in biotype 2) matched those from the NR database. BLASTX analysis of sequences with the highest E-values revealed that 59% of the biotype 1 sequences matched those of the pea aphid, Acyrthosiphon pisum. However, only 17% of the biotype 2 sequences were similar to those of A. pisum. RT-qPCR expression analyses confirmed that the biotype 2 gut transcriptome differs significantly from that of biotype 1. A transcript coding the tRNA-Leu gene was significantly up-regulated in the biotype 2 transcriptome, strongly suggesting that leucine metabolism is a critical factor in biotype 2 survival. Many more transcripts encoding protease inhibitors occurred in the avirulent biotype 1 gut than in the gut of virulent biotype 2. However, more protease transcripts occurred in the biotype 2 gut than in the biotype 1 gut, suggesting that the avirulent biotype produces protease inhibitors in response to plant proteases. The virulent biotype 2 produces trypsin-like and chymotrypsin-like serine protease counter-defenses to overcome biotype 1-resistant plants.
Citation: Anathakrishnan, R., Sinha, D. K., Murugan, M., Zhu, K. Y., Chen, M. S., Zhu, Y. C., & Smith, C. M. (2014). Comparative gut transcriptome analysis reveals differences between virulent and avirulent Russian wheat aphids, Diuraphis noxia. Retrieved from http://krex.ksu.edu
Keywords: Biotype; Diuraphis noxia; Phloem feeder; Plant resistance; Buchnera; Transcriptome analysis